Notoginsenoside R1 Protects Against the Acrylamide-Induced Neurotoxicity via Upregulating Trx-1-Mediated ITGAV Expression: Involvement of Autophagy - Wang, Wenjun; Huang, Lu; Thomas, Elizabeth Rosalind; Hu, Yingying; Zeng, Fancai; Li, Xiang (Frontiers in Pharmacology, 2020)
Acrylamide (ACR) is a common chemical used in various industries and it said to have chronic neurotoxic effects. It is produced during tobacco smoking and is also generated in high-starch foods during heat processing. Notoginsenoside R1 (NR1) is a traditional Chinese medicine, which is used to improve the blood circulation and clotting. The objective of this study was to investigate the mechanism of ACR-triggered neurotoxicity and to identify the protective role of NR1 by upregulating thioredoxin-1 (Trx-1). Our results have shown that NR1 could block the spatial and cognitive impairment caused by ACR administration. Bioinformatics analysis revealed that Trx-1 regulated autophagy via Integrin alpha V (ITGAV). NR1 could resist the ACR-induced neurotoxicity by upregulating thioredoxin-1 in PC12 cells and mice. The autophagy-related proteins like autophagy-related gene (ATG) 4B, Cathepsin D, LC3 II, lysosomal-associated membrane protein 2a (LAMP2a), and ITGAV were restored to normal levels by NR1 treatment in both PC12 cells and mice. Besides, we also found that overexpression of Trx-1 resisted ACR-induced autophagy in PC12 cells and downregulation of Trx-1 triggered autophagy induced by ACR in PC12 cells. Therefore, it could be concluded that Trx-1 was involved in the autophagy pathway. Besides, we also found that ITGAV was an intermediate node linking Trx-1 and the autophagy pathway.